The Role of Perceived Ease of Use and Customer Engagement In Influencing Behavioural Intention to Use Traveloka Paylater - Evelyne Austine Sugandi; Sabilla Saberina; Aggi Panigoro Sarifiyono (International Journal of Business, Economics, and Social Development, 2023)
The objective of this study were to find out the role of perceived ease of use and customer engagement in influencing behavioural intention to use Traveloka Paylater. Based on the increasing number of paylater services users in Indonesia, as well as the lack of behavioural intention to use Traveloka Paylater as the service from Traveloka, which incidentally is the number one online travel and lifestyle superapp in Indonesia. In this study, data were collected through the online questionnaire distribution to the respondents. The population in this study were users of Traveloka as seen from the number of users who gave ratings on PlayStore. The number of sampels taken based on calculations using Isaac and Michael formulas with a total sample are 271 (two hundred seventy one) respondents. The research method that used in this study is an associative quantitative method with a descriptive and verification approach. The result of the questionnaire distribution were analyzed by multiple regression analysis, coefficient of determination, t-test and F-test. The result of this study showed that: (1) perceived ease of use has a partial influence on behavioural intention to use Traveloka Paylate by 0,536 or 53%r. (2) customer engagement has a partial influence on behavioural intention to use Traveloka Paylater by 0,573 or 57,3%. (3) perceived ease of use and customer engagement has a stimultaneous on behavioural intention to use Traveloka Paylater by 0,680 or 68%.